Peripheral oxidative stress markers in diabetes‐related dementia. Issue 12 (4th November 2015) - Hatanaka, Hirokuni; Hanyu, Haruo; Fukasawa, Raita; Sato, Tomohiko; Shimizu, Soichiro; Sakurai, Hirofumi
Abstract : Aims: We previously found that there was a dementia subgroup with characteristics predominantly associated with diabetes mellitus (DM)‐related metabolic abnormalities, referred to as "diabetes‐related dementia (DrD)." We determined the possible role of oxidative stress in the pathophysiology of DrD. Methods: In a 2013 study, we classified 175 patients with clinically diagnosed Alzheimer's disease (AD) and DM into four subgroups based on brain imaging. Among them, we measured endogenous plasma anti‐oxidants, such as albumin, unconjugated bilirubin and uric acid, and urinary 8‐hydroxy‐2′‐deoxyguanosine and 8‐isoprostane in 58 patients of an AD group showing decreased regional cerebral blood flow of the parietotemporal lobe on single‐photon emission computed tomography (AD+DM group), and in 35 patients of a DrD group showing neither decreased regional cerebral blood flow of the parietotemporal lobe nor cerebrovascular disease on magnetic resonance imaging, which is strongly associated with DM‐related factors. A total of 31 patients with AD and without DM (AD−DM group) were enrolled as a control group. Results: The DrD group showed a significant decrease in plasma levels of anti‐oxidants, and a significant increase in urinary 8‐hydroxy‐2′‐deoxyguanosine and 8‐isoprostane levels in contrast to the AD−DM and AD+DM groups. Cognitive performance was negatively correlated with urinary 8‐hydroxy‐2′‐deoxyguanosine and 8‐isoprostane levels in the DrD group. Conclusions: These results strongly suggest that a decrease in anti‐oxidant levels and an increase in oxidative damage might be involved in the pathophysiology and cognitive decline associated with DrD.Geriatr Gerontol Int 2016; 16: 1312–1318.